Rechargeable Manganese Dioxide−Zinc Batteries: A Review Focusing on Challenges and Optimization Strategies under Alkaline and Mild Acidic Electrolyte Media. Issue 10 (9th August 2022) - Debnath, Subhrajyoti; Maiti, Apurba; Naskar, Pappu; Banerjee, Anjan
Abstract: Herein, we have reviewed the recent developments of rechargeable manganese dioxide−zinc (MnO2 −Zn) batteries under both alkaline and mild acidic electrolyte systems. The evolution pathway of MnO2 −Zn system from Leclanché cell to alkaline primary batteries and from primary to secondary batteries is chronologically depicted. Several adverse phenomena are associated with the reversibility of metallic zinc negative electrode under alkaline (pH 14) electrolyte mediums, and these may include zinc dendrite formation, passivation of electrode surface, shape change of the electrode, zincate crossover through separator and hydrogen evolution upon charging. The MnO2 positive electrode also experiences few performance degrading issues under alkaline mediums; like generation of electrochemically inert phases (Mn3 O4 and ZnMn2 O4 ) in the electrode upon deep‐discharge and Mn‐dissolution in the electrolyte. The mitigation measures of these challenges are well documented and systematically analysed. On the invention of zinc‐ion batteries, the MnO2 −Zn secondary batteries are assembled under mild acidic (pH 4–6) electrolytes, and eventually, several adverse effects of alkaline systems are drastically nullified. However, recent scientific and technical efforts are coined to address the challenges of large‐scale MnO2 −Zn batteries in mild acidic mediums, and formulate the optimization strategies. This review culminates with a few smart designs of MnO2 −Zn batteries, whereas, truly path‐breaking concepts are associated with. To the best of our knowledge, it is the first review that covers the entire spectrum of MnO2 −Zn system in both alkaline and mild acidic mediums, along with evolution pathways. Abstract : Several challenges are associated with MnO2 −Zn batteries, and these include zinc dendrite, electrode passivation, zincate crossover, H2 evolution, MnO2 structure disintegration, Mn‐dissolution etc. Such issues are mitigated by designing special electrodes, electrolytes and separators. However, present technology demonstrates both large scale and miniaturized devices for respective load‐levelling and flexible cum wearable electronics.